Recurrent Glioma With Lineage Conversion From Oligodendroglioma to Astrocytoma in Two Cases - Kim, Jo-Heon; Jang, Woo-Youl; Jung, Tae-Young; Jung, Shin; Kim, Kyung-Keun; Kim, Hyung-Seok; Kim, Eun-Hee; Lee, Min-Cheol; Moon, Kyung-Sub; Lee, Kyung-Hwa (Frontiers in Oncology, 2019)
Following the introduction of the molecular classification of gliomas by the WHO in 2016, molecularly-proven lineage conversion during glioma recurrence has never been reported. The reported two cases were initially diagnosed as oligodendroglioma with 1p/19q-codeletion and mutation of isocitrate dehydrogenase 1 (IDH1)-R132H. The recurrent tumors showed loss of alpha-thalassemia/mental retardation X-linked (ATRX) expression, strong P53 positivity, and 1p/19q-nondeletion. Next generation sequencing analysis performed on the first case confirmed the transition of molecular traits from oligodendroglioma to astrocytoma. An IDH mutation of R132H was preserved in the episodes of recurrence, but ATRX and TP53 mutations were newly acquired and TERT promoter mutation C228T was lost at the most recent recurrence. The issue in question for the presented cases is whether the original tumors were pure oligodendrogliomas that then transdifferentiated into astrocytomas, or whether the original tumor was an oligoastrocytoma having oligodendroglioma cells that outnumbered the astrocytoma cells and where the astrocytoma cells becoming more dominant over the episodes of recurrence. With the recognition of the possibility of lineage conversion, our study suggests that molecular examination should be performed to adjust therapeutic strategies in recurrent gliomas. Indeed, our observation of lineage conversion in glioma recurrence calls into question the current distinction drawn between oligodendroglioma, astrocytoma and oligoastrocytoma, rather than simply bidding “farewell to oligoastrocytoma”.